A population‐based study of hereditary non‐polyposis colorectal cancer: evidence of pathologic and genetic heterogeneity. (7th February 2013) - Warden, G; Harnett, D; Green, J; Wish, T; Woods, MO; Green, R; Dicks, E; Rahman, P; Zhai, G; Parfrey, P
Abstract : Hereditary non‐polyposis colorectal cancer (HNPCC) may be the result of Lynch syndrome (LS) caused by mutations in mismatch repair (MMR) genes, a syndrome of unknown etiology called familial colorectal cancer type‐X (FCCTX), or familial serrated neoplasia associated with the colorectal cancer (CRC) somatic BRAF mutation. To determine the cause of HNPCC in the founder population of the island of Newfoundland, we studied 37 families with LS and 29 families without LS who fulfilled the Amsterdam I criteria. In non‐LS, four index CRCs were BRAF mutation positive, one of which was microsatellite instable. Geographic clustering of LS families caused by three different founder mutations in MSH2 was observed. Nine unique MMR mutations in four MMR genes were identified in single families distributed in different geographic isolates. The geographic distribution of non‐LS was similar to LS. The coefficient of relatedness using genotype data was significantly higher for non‐LS than for all CRC. Extensive genealogic investigation failed to connect non‐LS families and in some clusters pathologic CRC heterogeneity was observed. We conclude that non‐LS HNPCC may be a heterogeneous disorder with different pathogenic pathways, and that the geographic distribution is consistent with multiple different mutations in unknown CRC susceptibility gene(s).